How does interactive case-based learning improve students' complex mathematical problem-solving abilities? - Miftah, Ramdani; Dahlan, Jarnawi Afghani; Kurniawati, Lia; Herman, Tatang; Lutfiana, Lutfiana (Universitas Papua, 2024)
Complex Mathematical Problem Solving (CMPS) is a crucial competency that equips students to navigate uncertain future situations. To enhance this skill, there is a need for more effective instructional models. One promising approach is Interactive Case-Based Learning (ICBL), an advanced iteration of the Case-Based Learning model. ICBL engages students with intricate real-world cases, enabling them to grasp mathematical concepts and adapt to novel and unfamiliar scenarios encountered in everyday life. This study aims to evaluate students' CMPS abilities following participation in ICBL-based instruction and to assess their responses to this instructional approach. A quasi-experimental design was employed, involving an experimental group and a control group. The participants were seventh-grade students studying sequences and series. The research utilized ICBL-based teaching materials, CMPS ability tests, and student response questionnaires. The study's findings are that students instructed using the ICBL model demonstrated superior CMPS abilities compared to those instructed using traditional methods, and students responded positively to the ICBL instructional model in mathematics learning. This research underscores that the ICBL model can significantly enhance students' ability to solve complex problems. Consequently, educators should consider incorporating the ICBL model into their teaching strategies, and curricula should be adapted to support its implementation.